Model Of Correlation Of Work Motivation and Organizational Commitment Through Workplace Spirituality and Servant Leadership - Amalia, Lia Amalia; Nurafian, Basman (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of Servant Leadership on Organizational Commitment through Workplace Spirituality and Work Motivation. The independent variable consists of Servant Leadership, the dependent variable is Organizational Commitment and the intervening variables are Workplace Spirituality and Work Motivation. This research was conducted on millennial-generation employees who worked for more than one year within Tangerang area. The samples used were 160 respondents with purposive sampling technique. This type of research is causal associative in nature and the method used in this research is Path Analysis. The results of this study indicate that Servant Leadership has positive and significant effect on Workplace Spirituality and Work Motivation. Workplace Spirituality and Work Motivation have a positive and significant effect on Organizational Commitment, while Servant Leadership does not have a positive and significant effect on Organizational Commitment. Workplace Spirituality and Work Motivation have successfully become the Intervening variables for Servant Leadership.